The Effectiveness of Technology-Based Islamic Religious Education Learning Media in Improving Motivation and Learning Outcomes of Elementary School Students - Novia Rizqiatul Umami; Dedi Djubaedi; Wakhid Nashruddin (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2025)
ABSTRACT This study aimed to analyze the effectiveness of technology-based Islamic Religious Education learning media in improving student motivation and learning outcomes at the elementary school. This study used a qualitative approach with a literature review. Data collection was carried out by reviewing articles related to technology-based Islamic Religious Education learning media in elementary schools published in the period 2020–2025. The analysis was carried out by reviewing 14 previous research results that discussed the use of various digital media. The results showed that the use of technology-based Islamic Religious Education learning media proved effective in increasing student interest, motivation, involvement, conceptual understanding, and learning outcomes. In addition, technology media was also able to strengthen religious values and provide a more contextual and enjoyable learning experience. However, the implementation of technology media still faced a number of challenges, such as limited teacher competence in using technology, limited infrastructure, dependence on internet access, and the need for content curation that was in accordance with Islamic teachings. Therefore, it was essential to offer training support, provide necessary facilities and infrastructure, and implement school policies that facilitated the optimal integration of technology media in Islamic Religious Education, particularly at the elementary school.